The Lord is good: seeking the God of the Psalter - Holmes, Christopher R. J. (Studies in Christian doctrine and scripture, 2018)
God is good. "Taste and see that the Lord is good," the Psalmist writes (Ps 34:8). And to those who called him good, Jesus said, "No one is good--except God alone" (Mk 10:18). In this volume in IVP Academic's Studies in Christian Doctrine and Scripture series, Christopher R.J. Holmes explores the divine attribute of God's goodness through a theological interpretation of the Psalter that engages with the church's rich tradition, including Augustine and Barth, but especially Aquinas. He contends that in the very depths of God's being, God is goodness itself and that goodness is preeminent among the divine attributes. Leading us in this journey through the Psalms and the church's tradition, Holmes helps us to understand what it means to make that simple affirmation: God is good